Clinical profile of culture proven enteric fever in children at university teaching hospital, Nepal - Shah, Ganesh; Ghimire, Amrit; Shrestha, Shrijana (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Enteric fever is one of the major public health issues in Nepal. The present study was designed to analyze the clinical profile and antibiotic sensitivity pattern in the cases of culture positive typhoid fever. Methods: This was a cross sectional study done by reviewing the hospital record files of children admitted in paediatric ward of Patan Hospital with culture positive enteric fever over a period of seven years from January 2007 to December 2013. The mode of presentation, sensitivity pattern of isolates from blood culture, response to therapy and the complications were recorded and analyzed. Results: There were total of 119 culture positive enteric fever admitted to children ward during this period, 64 (53.7%) males and 55 (46.3%) females. Common symptoms were fever (100%), vomiting 37 (31.09%), diarrhea 27 (22.68%), abdominal pain 31 (26%) cough 24 (20%), and constipation six (5%). Common clinical signs were hepatomegaly 41 (34.4%), splenomegaly 25 (21%), and chest signs 10 (8.4%). Sensitivity to ceftriaxone was 96.6% in this study. Ninety four percent of salmonella typhi in 2013 were resistant to quinolones. Conclusions: Fever, vomiting, abdominal pain, diarrhea and cough were major manifestations and encephalopathy was common complication of enteric fever in this study. Resistance to many of the drugs are emerging. An appropriate antibiotic has to be initiated only after culture sensitivity in typhoid fever. Journal of Patan Academy of Health Sciences. 2014 Dec;1(2):42-45